AB1069 Incidence of inpatient acute gouty arthritis flare and impact on length of hospital stay. (23rd January 2014) - Fisher, M.; Pieper, C.; Hassell, N.; Levens, J.; Fernandez, M.; Zacker, C.; Keenan, R.
Abstract : Background: Epidemiologic studies suggest that gout is prevalent in 4% of the general population, increasing in incidence, and associated with morbidity and mortality. Gout has been shown to have a significant economic impact and managed care burden. Although gout is thought of as an outpatient problem, it frequently occurs during inpatient hospitalizations. However, little data on the incidence of inpatient acute gout, impact on length of stay (LOS), and associated health care costs exists. Objectives: Quantify the incidence of gout occurring during hospitalization for other causes, and determine any associated differences in LOS. Methods: In this multi-center retrospective study (Massachusetts General Hospital and Duke University Health Systems), gout was identified among all admissions from 1 July, 2009- 31 December, 2010. Patients 18-100 years old were eligible for analysis if they had any one of 7 ICD-9 diagnoses of gout and were admitted for any diagnosis except acute gout. Patients were excluded if they expired during hospitalization. Admission diagnoses and length of stay were recorded and patients were classified as either acute inpatient gout flare with no history of gout, acute inpatient gout flare with a history of gout, and history of gout but no inpatient gout flare. Each chart was reviewed for accuracy of gout diagnosis and for evidence of an acute flare. An interim analysis of data gathered to date was conducted using SAS statistical software (version 9.3). Results: There were no differences in age or gender between the groups. There were differences in race, with an increase in African American patients in the group with an acute attack (p=0.002). Of 845 charts reviewed to date, 24 patients had an acute flare with no previous history of gout (2.8%). Of 801 patients with a history of gout, 206 had an acute flare during hospitalization (25.7% of patients with a history of gout, 24.4% of overall sample). The remaining 20 patients were found, on records review, to have no history of gout and no flare during hospitalization. Mean length of stay for patients with a history of gout but no flare was 6.3 days (SD 15.3). For patients with who had an episode of acute gouty arthritis during their hospital course, mean length of stay was 8.7 days (SD 9.4). The difference in mean length of stay between the two groups was 2.4 days (p<0.0001). Conclusions: Patients who experience acute gouty arthritis flares during admission tend to have longer LOS compared to those patients with a history of gout who did not have a flare. This may lead to greater economic burden on the patient and health care system compared to those without inpatient gout flares, as well as increased suffering on the part of these patients. Further research to identify specific risk factors for inpatient flares may allow preventive interventions. Our data are the first to quantify, in a U.S. population, the effect acute gouty arthritis has on LOS. Disclosure of Interest: M. Fisher Grant/Research support from: Investigator Initiated Support - Novartis, C. Pieper: None Declared, N. Hassell: None Declared, J. Levens: None Declared, M. Fernandez Employee of: Novartis Pharmaceuticals, C. Zacker: None Declared, R. Keenan Grant/Research support from: Novartis, Consultant for: Savient, Speakers Bureau: Novartis, Savient